Outpatient intravenous diuresis in a rural setting: safety, efficacy, and outcomes - Pathangey, Girish; D’Anna, Susan P; Moudgal, Rohitha A.; Min, David B.; Manning, Katharine A.; Taub, Cynthia C.; Gilstrap, Lauren G. (Frontiers in Cardiovascular Medicine, 2023)
Purpose To evaluate the safety, efficacy, and outcomes of outpatient intravenous diuresis in a rural setting and compare it to urban outcomes. Methods A single-center study was conducted on 60 patients (131 visits) at the Dartmouth-Hitchcock Medical Center (DHMC) from 1/2021–12/2022. Demographics, visit data, and outcomes were collected and compared to urban outpatient IV centers, and inpatient HF hospitalizations from DHMC FY21 and national means. Descriptive statistics, T-tests and chi-squares were used. Results The mean age was 70 ± 13 years, 58% were male, and 83% were NYHA III-IV. Post-diuresis, 5% had mild-moderate hypokalemia, 16% had mild worsening of renal function, and 3% had severe worsening of renal function. No hospitalizations occurred due to adverse events. The mean infusion-visit urine output was 761 ± 521 ml, and post-visit weight loss was −3.9 ± 5.0 kg. No significant differences were observed between HFpEF and HFrEF groups. 30-day readmissions were similar to urban outpatient IV centers, DHMC FY21, and the national mean (23.3% vs. 23.5% vs. 22.2% vs. 22.6%, respectively; p = 0.949). 30-day mortality was similar to urban outpatient IV centers but lower than DHMC FY21 and the national means (1.7% vs. 2.5% vs. 12.3% vs. 10.7%, respectively; p < 0.001). At 60 days, 42% of patients had ≥1 clinic revisit, 41% had ≥1 infusion revisit, 33% were readmitted to the hospital, and two deaths occurred. The clinic avoided 21 hospitalizations, resulting in estimated cost savings of $426,111. Conclusion OP IV diuresis appears safe and effective for rural HF patients, potentially decreasing mortality rates and healthcare expenses while mitigating rural-urban disparities.